A review of conceptual changes and perception studies of autism and related terminologies - LAO Uchong, ZHU Huilin (Xin yixue)
This review provides an overview of the evolution and perceptions of the concept of autism within Western and Chinese contexts， as well as the perceptions of various groups toward official and related terminology. It emphasize the importance of language in constructing social cognition and values of autism， offering a guide to the translation， interpretation and usage of autism-related languages in Chinese. The discourse in the West surrounding “person-first language” and “identity-first language” reflects divergent perspectives on identity within the autistic community. In the Chinese context， the discourse on autism is largely led by professionals， with societal understanding of autism often shaped by medical and charity perspectives. Different Chinese users construct and perceive autism-related terms in diverse ways. The medical terms “孤独症” （gūdú zhèng） and “自闭症” （zìbì zhèng） carry stigmatizing connotations， especially “zìbì zhèng，” which， due to its negative association with self-imposed isolation， is often linked with negative labels such as “dangers” or “burdens.” Terms like “星星的孩子” （xīngxīng de háizi） and “闭娃” （bì wá）， despite their popularity， are criticized by the autistic community for their romanticized and demeaning connotations， and for overlooking adult autistic individuals. The term “孤独症谱系障碍” （gūdú zhèng pǔxì zhàng’ài） is preferred for its lesser stigmatizing implications. Autistic individuals prefer neutral and non-pathologizing expressions. This review calls for discussions of autism in the Chinese context to focus on individual experiences， respect their subjectivity， reflect on potential ableist tendencies， and promote the concept of neurodiversity， to foster a more comprehensive and inclusive societal understanding and acceptance of autistic people.